2005
DOI: 10.1002/jmv.20392
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of acute hepatitis C in Cairo, Egypt

Abstract: Surveillance of acute hepatitis has been set up in two fever hospitals in Cairo to diagnose acute hepatitis C. Patients were categorized as definite acute hepatitis C with positive hepatitis C virus (HCV) RNA and without anti-HCV antibody, or probable acute hepatitis C with positive HCV RNA, positive anti-HCV antibody, alanine aminotransferase >/=4 times the upper limit of normal (ULN), and high risk parenteral exposure in the 1--3 months prior to the beginning of symptoms. From May to November 2002, 315 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 16 publications
0
36
0
Order By: Relevance
“…The potential mode of transmission of HCV through occupational exposures and parenteral anti-schistosomal therapy (PAT) has also been discussed [28,29]. Some investigations aimed at determining aflatoxin levels in food items in Egypt produced conflicting results [16,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…The potential mode of transmission of HCV through occupational exposures and parenteral anti-schistosomal therapy (PAT) has also been discussed [28,29]. Some investigations aimed at determining aflatoxin levels in food items in Egypt produced conflicting results [16,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Recent investigations in Egypt have also shown the increasing importance of HCV infection in the etiology of HCC, now estimated to account for 40-50% of cases.…”
mentioning
confidence: 99%
“…20,21 Recent investigations in Egypt have also shown the increasing importance of HCV infection in the etiology of HCC, now estimated to account for 40-50% of cases. [6][7][8] The future of HCC in Egypt and the magnitude of its socio-economic burden will be a legacy of the country's unique HCV epidemic and the shifting dynamics of HBV and HCV.…”
mentioning
confidence: 99%
“…In another study with 12 cases in Egypt, risk factors of acute hepatitis C were reported as dental applications in 5 patients, use of IV drugs in 2 patients. Whereas in 5 cases parenteral contact was not determined [12]. Although risk factors were nearly similar the order of factors may vary in different regions of the world.…”
Section: Discussionmentioning
confidence: 99%